216 LIPOPOLYSACCHARIDE INHIBITS Fibroblast Growth Factor-10 EXPRESSION IN FETAL MOUSE LUNG MESENCHYME. (1st January 2006) - Benjamin, J. T.; Smith, R.; Davis, N.; Prince, L. S.
Abstract : Purpose of Study: Prenatal exposure to inflammation increases the risk of bronchopulmonary dysplasia (BPD) in preterm infants. In a fetal mouse lung model, lipopolysaccharide (LPS) decreased distal airway branching, which may contribute to BPD pathology. In a candidate gene approach, we tested if LPS decreased expression of FGF-10, a master regulator of branching morphogenesis. We hypothesized that decreased FGF-10 expression could lead to defective distal airway branching. Methods: E16 fetal mouse lung explants were cultured for up to 72 hours. Distal airway branching was measured by counting the number of distal airways per explant area. Fetal mouse lung mesenchymal cells were also isolated and cultured. Gene expression was measured by real time PCR. Results: We measured decreased FGF-10 gene expression in LPS-treated fetal lung explants (55% of control, p < .05). LPS did not alter FGF-10 expression in explants from TLR4 mutant mice. Recombinant FGF-10 increased the number of distal airway branches from 40.2 branches/mm 2 to 49.6 branches/mm 2 (p < .05). Blocking FGF-10 signaling with a polyclonal anti-FGF10 antibody inhibited distal airway branching (30.2 branches/mm 2, p < .01); anti-FGF-10-treated explants resembled those exposed to LPS. We restored distal airway branching in LPS-treated explants by adding exogenous FGF-10, thus supporting our hypothesis. LPS also decreased the expression of the FGF-10-induced genes BMP4, BMPR1a, and PERP but did not change the expression of FGF-7-related genes. LPS had no effect on FGF-10 expression in isolated mesenchymal cells, suggesting that epithelial-mesenchymal interactions were required. The effect of LPS on FGF-10 expression did not appear to require TGFb1, which regulates FGF-10 in other models. Conclusion: LPS decreased FGF-10 expression and altered gene expression along the FGF-10 signaling pathway. Decreased FGF-10 expression may identify a mechanism by which innate immunity can contribute to BPD.